2021
DOI: 10.3390/app11125546
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Action under Different Stimulus Presentations: A Review of Eye-Tracking Studies with an Extended View on Possibilities of Virtual Reality

Abstract: Visual anticipation is essential for performance in sports. This review provides information on the differences between stimulus presentations and motor responses in eye-tracking studies and considers virtual reality (VR), a new possibility to present stimuli. A systematic literature search on PubMed, ScienceDirect, IEEE Xplore, and SURF was conducted. The number of studies examining the influence of stimulus presentation (in situ, video) is deficient but still sufficient to describe differences in gaze behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Moreover, it was found that different perspectives lead to variations in the attention placed on AOIs, underscoring the necessity and importance of studying defense anticipation from various perspectives. With the advancement of technology, virtual reality combined with eye-tracking devices can be used to create more immersive and repeatable scenarios, enriching the empirical research on eye movements in volleyball [ 63 , 64 ]. However, the present study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that different perspectives lead to variations in the attention placed on AOIs, underscoring the necessity and importance of studying defense anticipation from various perspectives. With the advancement of technology, virtual reality combined with eye-tracking devices can be used to create more immersive and repeatable scenarios, enriching the empirical research on eye movements in volleyball [ 63 , 64 ]. However, the present study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The regression count reflects the participant's reprocessing of previous information. It provides information about how many times the participant returned their gaze to a specific target in a specific area of interest, which allows researchers to examine which areas repeatedly attract participants (regardless of whether they are good or bad), and which areas are seen and then moved [38]. Although eye tracking cannot indicate users' psychological feelings when looking at something, it can provide detailed processing data for research to analyze the attractiveness of things.…”
Section: ) Regression Countmentioning
confidence: 99%
“…However, there is, as yet insufficient, commensurate capacity for remote action. Again, H/E understanding informs us of the dangers and shortfalls that accrue when perception-action links are broken (and see Flach et al, 1995;Hancock et al, 1995;Heilmann & Witte, 2021).…”
Section: The Panopticon Principle: Rendering Existential Threats Asmentioning
confidence: 99%